Kinect : realibility of hand-eye coordination among rugby players using consumer depth camera - Rozan, Mohd. Razmi (2014)
Rugby is a growing sport in the whole world. For athletes who want to achieve a high level of potential, such as hand coordination skills and speed of reaction (sport) both are expected to be in good performance. The main problem in many sports is that there is no test for the reliability of the developed test tools. Thus, the aim of this study is to determine the reliability of the tests, so the research was conducted twice with an interval of 6-7 days (test-retest). A total of 33 rugby players (16-18 years of age) have participated in the study. The analysis includes one motor tasks performed only with the use of KIHECT©. Thus, this study was conducted on a differentiated time and score through two methods of evaluation test: automatically and manually in order to obtain the level of reliability of the tools. The hardware and software that were used in this research are Kinect camera 360, windows SDK and computer or monitor use by CPU systems. The average values of the resultant p-values (<0.005) showed that the instrument is reliable and practical to be used in research area. A test on KIHECT© displayed sufficient reliability to see the difference in score data using automatic method (evaluation score using KIHECT©) and manual method (evaluation score of the two observers). Therefore, it can be implemented as a tool to train the hand-eye coordination in rugby games.